Frequency Doubled Nd: YAG Laser for the Treatment of Diabetic Retinopathy - Al-Zubadi, Nagham S. (Iraqi Journal of Laser, 2003)
The present study was conducted with a view to determine whether focal laser therapy result in visual recovery and regression of macular edema in patients with non proliferative diabetic retinopathy and maculopathy ,and whether combined focal and scatter laser therapy in patients with proliferative diabetic retinopathy and maculopathy results in visual recovery ,regression of macular edema and regression of the risk factors. In the present work, a frequency doubled Nd: YAG laser was used for the treatment of diabetic retinopathy. The study evaluates 41 eyes of 33 diabetic patients both with Insulin Dependent Diabetes Mellitus IDDM, (n=16) and Non Insulin Dependent Diabetes Mellitus NIDDM, (n=17) with diabetic retinopathy divided into two groups. Maculopathy was regressed in 32/41 treated eyes, 23/24 with maculopathy and non-proliferative diabetic retinopathy are treated by grid laser photocoagulation, 9/17 with proliferative diabetic retinopathy and maculopathy are treated by grid combined with pan retinal photocoagulation. Maculopathy was unchanged in 7/41, deterioration in 2/41. Visual acuity improved in 8/41 patients one line of Snellen chart in young patients with shorter duration and non- proliferative diabetic retinopathy, and good visual acuity prior to therapy and 31/41 stabilized visual acuity for the follow up period, 2/41 deterioration of visual acuity by one line of Snellen chart with progression of edema, hemorrhage and exudation, 3/41 patients complain of paracentral scotoma one-week post treatment improved gradually after 2 weeks. Higher power density is needed to treat the diffuse form of maculopathy regarding the severity of maculopathy and macular edema. The power density needed to have the desired effect is less in more pigmented fundus than in fair fundus in order to have the same effect.